1988
DOI: 10.1128/jb.170.5.2374-2378.1988
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of cytoplasmic proline levels in Salmonella typhimurium: effect of osmotic stress on synthesis, degradation, and cellular retention of proline

Abstract: I investigated the effects of osmotic stress on the synthesis and catabolism of proline in Salmonella typhimurium by measuring the intracellular and extracellular proline levels in various strains. In the wild-type strain, exposure to 0.8 M NaCl did not cause a significant change in the intracellular proline level; however, it brought about a 6.5-fold increase in the intracellular glutamate pool size. These results indicate that 'y-glutamyl kinase is inhibited by proline in wild-type cells in media of normal o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
33
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 19 publications
2
33
0
Order By: Relevance
“…4). The data presented by Csonka (1988) raise the interesting possibility that the efflux system for glycine betaine and proline is active at low osmolarity and that its activity is diminished at high osmotic pressure. The combination of activation of the uptake system and inhibition of the efflux system by high osmotic pressure would control the accumulation of the compatible solutes glycine betaine and proline.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…4). The data presented by Csonka (1988) raise the interesting possibility that the efflux system for glycine betaine and proline is active at low osmolarity and that its activity is diminished at high osmotic pressure. The combination of activation of the uptake system and inhibition of the efflux system by high osmotic pressure would control the accumulation of the compatible solutes glycine betaine and proline.…”
Section: Discussionmentioning
confidence: 94%
“…However, early experiments to demonstrate activation of K+ efflux by high turgor created by downshock were similarly unsuccessful (Meury et al, 1985). It has been reported that osmotic pressure controls the amount of proline that is excreted into the medium by mutants of S. typhimurium that are osmotolerant due to overproduction of proline (Csonka, 1988). At low osmolarity excretion is high but at higher osmolarity the proline is retained by the cells.…”
Section: Discussionmentioning
confidence: 99%
“…During anaerobic growth, proline (71.9 nmol ml Ϫ1 OD 550 unit Ϫ1 ) was the only osmolyte above our limit of detection (Յ4.0 nmol ml Ϫ1 OD 550 unit Ϫ1 ). Since allosteric regulation prevents the biosynthesis of proline as an osmoprotectant (12,41,42), it is likely that corn steep liquor is also the source of intracellular proline. Supplementing CSL medium with additional proline (17 mM) had no effect on cell growth or volumetric productivity despite a 14% increase in the intracellular pool.…”
Section: Resultsmentioning
confidence: 99%
“…Proline transport, however, does not result, even under osmotic stress conditions, in high intracellular proline pools (14). Proline is endogenously synthesized from glutamate by the proA, proB, and proC gene products, which are synthesized at similar levels regardless of the availability of proline (7). Proline synthesis is negatively regulated through feedback inhibition of the first biosynthetic enzyme of the pathway, the proB gene product ␥-glutamylkinase (2).…”
mentioning
confidence: 99%